Mumps, Cervical Zoster, and Facial Paralysis: Coincidence or Association?. (6th February 2014) - Kondo, Kenji; Kanaya, Kaori; Baba, Shintaro; Yamasoba, Tatsuya
Abstract : The association of mumps with peripheral facial paralysis has been suggested, but its pathogenesis remains unclear. An 8-year-old girl simultaneously developed left peripheral facial paralysis, ipsilateral cervical herpes zoster, and bilateral mumps sialadenitis. Elevated anti-mumps and anti-varicella zoster virus IgM antibodies in serological testing indicated recent infection of mumps and reactivation of VZV. Molecular studies have provided mounting evidence that the mumps virus dysregulates the host's immune system and enables the virus to proliferate in the infected host cells. This dysregulation of the immune system by mumps virus may have occurred in our patient, enabling the latent VZV infection to reactivate.